2017
DOI: 10.18632/oncotarget.19850
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole decreases dialysis risk and improves survival in patients with pre-dialysis advanced chronic kidney disease

Abstract: IntroductionDipyridamole decreases proteinuria and improves renal function progression in patients with glomerular disease through its inhibition of platelet activation and enhanced nitric oxide expression. Few studies have evaluated the effects of dipyridamole on renal outcome or survival in CKD stage 5 patients who have not yet received dialysis (CKD 5 ND).Materials and MethodsA prospective cohort study was conducted based on the Taiwan National Health Insurance Research Database. From January 1, 2000 to Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Besides having inhibitory action on PDE 3 enzyme, this drug also inhibits uptake of adenosine leading to additional inhibition of platelet aggregation owing to this there is enhancement of nitric oxide expression helping in reduction of proteinuria and improves renal function progression in patients with kidney disease. 15 USES: prevention and prophylaxis of thromboembolism in patients with prosthetic heart valves and are on warfarin, reduces risk of long-term hemodialysis in chronic kidney disease, potential for protecting tissue from oxidative and metabolic stress. 16,17 S/E: coronary steal phenomenon, tachycardia, gastrointestinal distress, postural hypotension.…”
Section: Pd3mentioning
confidence: 99%
“…Besides having inhibitory action on PDE 3 enzyme, this drug also inhibits uptake of adenosine leading to additional inhibition of platelet aggregation owing to this there is enhancement of nitric oxide expression helping in reduction of proteinuria and improves renal function progression in patients with kidney disease. 15 USES: prevention and prophylaxis of thromboembolism in patients with prosthetic heart valves and are on warfarin, reduces risk of long-term hemodialysis in chronic kidney disease, potential for protecting tissue from oxidative and metabolic stress. 16,17 S/E: coronary steal phenomenon, tachycardia, gastrointestinal distress, postural hypotension.…”
Section: Pd3mentioning
confidence: 99%
“…In patients with kidney disease, dipyridamole reduces proteinuria and improves renal function by inhibiting platelet activation and enhancing nitric oxide (NO)-induced vasodilation. A prospective study of >28,000 patients with advanced chronic kidney disease (CKD) in Taiwan found that dipyridamole significantly reduced the risk of progression to long-term dialysis and predialysis death (hazard ratios 0.96 and 0.91, respectively; both P<.05 versus nonuse) [76]. In another large Taiwanese study in patients with advanced CKD, dipyridamole decreased the risk of progression to end-stage renal disease by approximately 15% and reduced all-cause mortality by 23.5% (P=.001) [77].…”
Section: Renoprotective Effectsmentioning
confidence: 99%
“…Beyond these antiviral effects, dipyridamole has shown anti-inflammatory, antioxidant, and vasodilatory activity [30][31][32][33][34], and is one component of a widely used anticoagulant (citrate-theophylline-adenosine-dipyridamole [CTAD]) [35][36][37]. Clinically, cardioprotective effects have been reported in patients with chronic heart failure [38], and improved renal function is documented in patients with chronic kidney disease, delaying risk of progression to dialysis and reducing mortality [39,40].…”
mentioning
confidence: 99%